Environmental Protection on the Example of Agricultural Lands - Kovach, Denys L.; Brulevych, Volodymyr V.; Levada, Olena V. (International Journal of Criminology and Sociology, 2021)
Agricultural land is the most valuable resource of today because the issue of food security in the world community now comes first. Unfortunately, the ecological condition of lands suitable for agricultural use in Ukraine and the situation in the field of their use is constantly deteriorating. The quality of land resources is declining and approaching catastrophic levels. In this regard, the purpose of the study is to explore the main aspects of legal and environmental regulation of fertile land protection and to suggest ways to improve the protection and preservation of agricultural land. The main research method is the method of analysis, thanks to which the world experience in the field of environmental protection in general and the protection of agricultural lands was comprehensively analysed. The normative-legal acts of Ukraine, which regulate the issues of land use, as well as protection and preservation of agricultural lands, were analysed. The proposed mechanisms of environmental protection on the example of agricultural lands can be used to form targeted government programs.